2017
DOI: 10.1007/s00701-017-3385-8
|View full text |Cite
|
Sign up to set email alerts
|

An introduction and overview of machine learning in neurosurgical care

Abstract: ML has started to find applications aimed at improving neurosurgical care by increasing the efficiency and precision of perioperative decision-making. A thorough validation of specific ML models is essential before implementation in clinical neurosurgical care. To bridge the gap between research and clinical care, practical and ethical issues should be considered parallel to the development of these techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 61 publications
1
109
0
1
Order By: Relevance
“…and epilepsy. 3,14,17,19,23,24,26 Memarian et al reported that the multimodality of ML, including linear discriminant analysis, naive Bayes (NB), and support vector machines, has high accuracy in surgical outcome prediction in patients with mesial temporal lobe epilepsy. 15,17 Moreover, Armañanzas et al demonstrated that ML algorithms such as NB, logistic regression, and k-nearest neighbors (k-NN) may be powerful methods of selecting surgical candidates who have a high likelihood of remaining free from seizures in temporal lobe epilepsy.…”
mentioning
confidence: 99%
“…and epilepsy. 3,14,17,19,23,24,26 Memarian et al reported that the multimodality of ML, including linear discriminant analysis, naive Bayes (NB), and support vector machines, has high accuracy in surgical outcome prediction in patients with mesial temporal lobe epilepsy. 15,17 Moreover, Armañanzas et al demonstrated that ML algorithms such as NB, logistic regression, and k-nearest neighbors (k-NN) may be powerful methods of selecting surgical candidates who have a high likelihood of remaining free from seizures in temporal lobe epilepsy.…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is the first study describing the use of an ANN to predict surgical resectability in patients with GBM. However, machine learning has been used elsewhere for neurosurgical outcome prediction in patients with brain tumours and other conditions such as neurovascular disease, epilepsy, movement disorders, traumatic brain injury, and hydrocephalus 8,19,20 . A recent systematic review has found that machine learning models perform significantly better than logistic regression, with a median absolute improvement in the AUC and accuracy of 0.06 and 15% respectively 8 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ANNs have been shown to robustly predict complications, outcomes, and prognosis among numerous fields, 5,13,31,[34][35][36] including TBI. 8,18,26,32,37,38 Thus, an ANN tool yielding predictive information concerning CRTBI would be helpful and provide an evidence-based mechanism for treating these patients. ANNs are computational constructs used to interpret the maximum number of combinations of data in complex systems, such as making medical diagnoses in neurosurgery, 36,37 where many competing factors influence outcome.…”
Section: Discussionmentioning
confidence: 99%